Peningkatan Kemampuan Public Speaking melalui Metode Pelatihan Kader Pada Organisasi IPNU/IPPNU Pac Balen Bojonegoro - Zaini Miftah; Muthi, Ahmad (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Communication is very essential in human life, because without communication it is impossible for a human being to be able to live his life as a social being. Public speaker is someone who has the ability to influence people and convey interesting information in front of many people such as preachers or presenters in seminars. The success or failure of a public speaker is caused by how he can communicate all the information about what he conveys. The purpose of this training is to equip the methods used in IPNU/IPPNU cadre training so that they can improve public speaking skills. The output of this activity is to equip IPNU/IPPNU cadres to become cadres who have the ability in public speaking, as well as a forum for NU students and santri to gather to continue the spirit and values ​​of nahdliyin, as well as a forum for student and santri communication to raise ukhuwah Islamiyah and Islamic symbols. This training shows very good results in accordance with the specified achievement indicators.